2022
DOI: 10.18502/ijph.v51i7.10092
|View full text |Cite
|
Sign up to set email alerts
|

Extremity Injuries during Sporting Activities According to Life Course: Focusing on Fractures

Abstract: Background: The increased participation in sports has led to an increased number of sports-related injuries. We aimed to identify the incidence of sports-related injuries by life course and the risk factors for sports-related extremity fractures. Methods: We analyzed data of patients with sports-related extremity injuries from Emergency Department-based national injury surveillance systems, obtained from Jan 2013 to Dec 2016. A multiple logistic regression analysis was performed to identify risk factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…However, for SRFs, the incidence in males and females was reported to be 261/10 5 and 35/10 5 , respectively [ 12 ]. Previous studies reported that the comparatively higher number of sports injuries in males may be explained by the higher percentages of men participating in sports [ 9 , 10 , 14 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for SRFs, the incidence in males and females was reported to be 261/10 5 and 35/10 5 , respectively [ 12 ]. Previous studies reported that the comparatively higher number of sports injuries in males may be explained by the higher percentages of men participating in sports [ 9 , 10 , 14 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the three sports that were most associated with SRFs in the geriatric population were outdoor walking, outdoor biking, and mountain hiking, which are all outdoor activities. Sports that cause SRFs in adolescents and adults include high-level activities such as football, rugby, skiing, snowboarding, hockey, and basketball [ 9 , 10 ]. Because there are differences between the sports that the elderly population frequently participates in and the sports in which SRFs frequently occur, additional research on the incidence of SRFs by sports type is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation